A Novel Polymorphism in the Promoter of the CYP4A11 Gene Is Associated with Susceptibility to Coronary Artery Disease. (1st February 2018) - Sirotina, Svetlana; Ponomarenko, Irina; Kharchenko, Alexander; Bykanova, Marina; Bocharova, Anna; Vagaytseva, Kseniya; Stepanov, Vadim; Churnosov, Mikhail; Solodilova, Maria; Polonikov, Alexey
Abstract : Enzymes CYP4A11 and CYP4F2 are involved in biosynthesis of vasoactive 20-hydroxyeicosatetraenoic acid and may contribute to pathogenesis of coronary artery disease (CAD). We investigated whether polymorphisms of the CYP4A11 and CYP4F2 genes are associated with the risk of CAD in Russian population. DNA samples from 1323 unrelated subjects (637 angiographically confirmed CAD patients and 686 age- and sex-matched healthy individuals) were genotyped for polymorphisms rs3890011, rs9332978, and rs9333029 of CYP4A11 and rs3093098 and rs1558139 of CYP4F2 by using the Mass-ARRAY 4 system. SNPs rs3890011 and rs9332978 of CYP4A11 were associated with increased risk of CAD in women: OR = 1.26, 95% CI: 1.02–1.57, P = 0.004, andQ = 0.01 and OR = 1.45, 95% CI: 1.13–1.87, P = 0.004, andQ = 0.01, respectively. Haplotype G-C-A of CYP4A11 was associated with increased risk of CAD (adjusted OR = 1.41, 95% CI: 1.12–1.78, andP = 0.0036 ). Epistatic interactions were found between rs9332978 of CYP4A11 and rs1558139 of CYP4F2 (P i n t e r a c t i o n = 0.025 ). In silico analysis allowed identifying that SNP rs9332978 is located at a binding site for multiple transcription factors; many of them are known to regulate the pathways involved in the pathogenesis of CAD. This is the first study in Europeans that reported association between polymorphism rs9332978 of CYP4A11 and susceptibility to coronary artery disease.